Evaluation of teaching factory using CIPP (Context, Input, Process, Product) model to improve vocational high school students' skills - Yoto Yoto; Marsono Marsono; Abdul Qolik; Achmad Romadin (Jurnal Pendidikan Vokasi, 2024)
Teaching Factory (TEFA) is a program that provides a real learning experience for students. Students are taught simulation of job sheet practice, management, marketing, and entrepreneurship. This research examines the feasibility of teaching factories regarding context, input, process, and product. This research uses mixed methods, namely qualitative research supported by descriptive quantitative data. The research was conducted in vocational high schools in East Java Province, Indonesia. The population of this research used a sample size based on the empirical formula from Isaac and Michael. The results showed that: (1) Based on the context, the teaching factory follows the vision and mission of the school and the demand from the community, business, and industry. Production planning achieved a score of 2.825 with a good category, based on the learning questionnaire; (2) Teaching factory learning in VHSs is appropriate in terms of the readiness of buildings and teachers by VHSs, the completeness of facilities, and the readiness of students in attitudes and competencies to get a score of 2.855 with a good category; (3) Based on the process, the learning is appropriate in terms of workshop layout, student activities, product quality control, and practical activities getting a score of 2.825 with a good category; and (4) The evaluation results, concluded that the learning is appropriate in terms of workshop layout, student activities, product quality control, and practical activities getting a score of 2.855 with a good category. The results of this evaluation study can be used to contribute to developing and improving existing programs to make them better.